ANALYSIS OF CONSUMER PREFERENCES IN PURCHASING SKINCARE BRAND OGANIC IN MATARAM CITY - Pratama, Dika; Wathoni, Nurtaji; Suparyana, Pande Komang (Institute of Computer Science (IOCS), 2025)
The growth of the beauty industry in Indonesia has increased competition among skincare brands, including local producers striving to differentiate themselves through product innovation. However, local brands such as OGANIC still face challenges in understanding the specific attributes that most influence consumer purchasing decisions, especially in urban markets like Mataram City. OGANIC is a local company brand engaged in the beauty industry, specifically in the production and development of organic skincare products. The natural ingredients used in this product include spirulina, seaweed, and premium pearl extract, all of which are natural ingredients with great potential available in the Lombok Island region. This study aims to determine what attributes are preferred by consumers and the attributes that consumers consider most when deciding to purchase OGANIC skincare in Mataram City. The determination of respondents as a sample was carried out by accidental sampling with a total of 50 respondents who purchased the product. The data obtained were analyzed using conjoint analysis. Based on the analysis results, consumers' main preferences for OGANIC skincare are those that contain natural ingredients, have a price above Rp. 100,000, are national brands, use glass bottles and are used by influencers. The OGANIC skincare attributes that consumers consider most in making purchases, sequentially based on importance, are ingredients, price, brand, product reputation, and packaging. It is expected that from the results of this study, manufacturers should improve the performance of OGANIC skincare attributes that are considered less important in their influence and maintain the performance of attributes that are considered important according to what consumers feel. This finding contributes scientifically by providing a conjoint analysis consumer preference model that can be used for the development of more competitive OGANIC brand skin care product strategies.